2022
DOI: 10.1302/2633-1462.31.bjo-2021-0175.r1
|View full text |Cite
|
Sign up to set email alerts
|

Association between sagittal spinopelvic alignment and femoral head destruction in the early stage of rapidly destructive coxopathy

Abstract: Aims This study aimed to evaluate sagittal spinopelvic alignment (SSPA) in the early stage of rapidly destructive coxopathy (RDC) compared with hip osteoarthritis (HOA), and to identify risk factors of SSPA for destruction of the femoral head within 12 months after the disease onset. Methods This study enrolled 34 RDC patients with joint space narrowing > 2 mm within 12 months after the onset of hip pain and 25 HOA patients showing femoral head destruction. Sharp angle was measured for acetabular coverage e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Morphological factors associated with the appearance of RPOH have recently been described by some authors, such as increased pelvic tilt, alteration of lumbar lordosis [13], decreased sacral slope, and spinopelvic mismatch as sagittal spinopelvic malalignment [14] like the increased Tönnis angle, Wiberg angle, or acetabular extrusion index.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological factors associated with the appearance of RPOH have recently been described by some authors, such as increased pelvic tilt, alteration of lumbar lordosis [13], decreased sacral slope, and spinopelvic mismatch as sagittal spinopelvic malalignment [14] like the increased Tönnis angle, Wiberg angle, or acetabular extrusion index.…”
Section: Discussionmentioning
confidence: 99%
“…Improper pressure induced by these pathological alignments may facilitate the localized accumulation of microdamage, potentially leading to SIFFH and SIFK. The etiology of both SIFK and SIFFH involves subchondral bone fragility [162,172] and distinctive morphological characteristics such as meniscal tears [167], an inverted acetabular labrum [195,196], knee varus alignment [168], hip dysplasia [193], and pelvic tilt [200]. Fragility, morphology, and fracture size accelerate collapse, leading to articular surface deformities.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, SIFFH can progress to advanced OA or RDC due to femoral head collapse, ultimately necessitating THA [181,182,197]. Older age [178], female sex [174], the location [198] and length [199] of the fracture line as observed on MRI, biomarkers of joint space narrowing [175], pelvic tilt [200], and pelvic range of motion [201] have been identified as risk factors for SIFFH progression. Thus, subchondral bone fragility, fracture severity, and mechanical overload may be involved in SIFFH pathogenesis.…”
Section: Risk Factor and Pathogenesismentioning
confidence: 99%
“…Ike et al 2 found that hip motion increases following THA. Onishi et al 18 found that patients with rapidly destructive hip OA and therefore significant bone loss had altered standing sagittal parameters compared to patients without significant bone loss, although they only reported static measurements. Buckland et al 9 studied the effect hip OA on spinopelvic biomechanics.…”
Section: Discussionmentioning
confidence: 99%